Błąd i niepewność pomiaru - Jenek, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses guidelines for estimating measurement uncertainty and differences between a measurement uncertainty and a measurement error. A measurement is always burdened with some uncertainty, which may be a result of instrument`s technical limitations, a result of measurement method applied or other factors. This paper describes methods of calculating uncertainty depending on the type of measurement applied. It also discusses basic issues related to making decisions with regards to conformity assessment of the product with the specification and basic information related to statistical distributions used in metrology. All topics presented in this paper are illustrated with examples, which in a practical way help to further explain the issues presented in this work.
Keywords: błąd pomiaru; niepewność pomiaru; ocena zgodności; measurement error; measurement uncertainty; conformity assessment